2018
DOI: 10.1016/j.jcmgh.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Human Gastrointestinal Cultures to Study the Microbiome and Infectious Diseases

Abstract: New models to study the intestine are key to understanding intestinal diseases and developing novel treatments. Intestinal organ-like culture systems (organoids and enteroids) have substantially advanced the study of the human gastrointestinal tract. Stem cell–derived cultures produce self-organizing structures that contain the multiple differentiated intestinal epithelial cell types including enterocytes, goblet, Paneth, and enteroendocrine cells. Understanding host–microbial interactions is one area in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 68 publications
0
78
0
Order By: Relevance
“…Dietary tryptophan that is metabolized by both host and bacteria to indole derivatives have been shown to reduce intestinal permeability in T84 cells (Jennis et al, 2018 ). Intestinal organoids have proven to be a good model to examine mechanisms of host-bacterial interactions in a multi-cellular system (Rothschild et al, 2016 ; Blutt et al, 2018 ). Polyphenol metabolites which are biotransformed by the gut microbiota, have also been examined in vitro models (mainly Caco-2) including urolithin A (Gonzalez-Sarrias et al, 2015 ) and tert-butyl hydroperoxide (Deiana et al, 2010 ) and 3,4-dihydroxyphenyl-ethanol (Manna et al, 1997 ).…”
Section: Other Potentially Useful Modelsmentioning
confidence: 99%
“…Dietary tryptophan that is metabolized by both host and bacteria to indole derivatives have been shown to reduce intestinal permeability in T84 cells (Jennis et al, 2018 ). Intestinal organoids have proven to be a good model to examine mechanisms of host-bacterial interactions in a multi-cellular system (Rothschild et al, 2016 ; Blutt et al, 2018 ). Polyphenol metabolites which are biotransformed by the gut microbiota, have also been examined in vitro models (mainly Caco-2) including urolithin A (Gonzalez-Sarrias et al, 2015 ) and tert-butyl hydroperoxide (Deiana et al, 2010 ) and 3,4-dihydroxyphenyl-ethanol (Manna et al, 1997 ).…”
Section: Other Potentially Useful Modelsmentioning
confidence: 99%
“…Enteroids can support replication of human rotavirus strains [ 91 ] and have also been successfully used to culture norovirus [ 92 ]. They are also slowly becoming robust enough to survive the addition of simple bacterial cultures or their supernatants [ 93 ]. While missing adaptive immunity, lymphatics, and complex microbiota, the system permits elegant and simplified examination of rotavirus–bacterial–innate immune interactions [ 94 ].…”
Section: Rotavirus Vaccines: a Case Studymentioning
confidence: 99%
“…The gut microbiome plays a key role in various aspects of human health including nutrient digestion and metabolism, development and maturation of immune system, protection from infections, nervous system development, and has widespread influence beyond the gastrointestinal tract ( Blanton et al, 2016 ; Kho and Lal, 2018 ). Numerous clinical studies have demonstrated the association of gut microbes with a wide array of cardiometabolic and chronic diseases including obesity, type 2 diabetes, atopic diseases, cardiovascular diseases, hypertension, anxiety, depression, bowel diseases, diarrhea, constipation, and brain diseases including Parkinson’s, Alzheimer’s, and others ( Bakhtiar et al, 2013 ; Cojocaru and Chicos, 2014 ; Althani et al, 2016 ; Coit and Sawalha, 2016 ; Scher et al, 2016 ; Davis and Bajaj, 2017 ; Gundogdu and Nalbantoglu, 2017 ; Ipci et al, 2017 ; Ruiz-Rodriguez and Rello, 2017 ; Shivaji, 2017 ; Blutt et al, 2018 ; Davidson and Epperson, 2018 ). However, given the practical and ethical complexity of performing invasive sampling procedures in human subjects, high inter-individual variation in the diets and in the gut microbiomes of humans, and relative ease of using animals with controlled diets for large scale mechanistic and genotypic research studies, different types of animals models including rodents (mice, rats, guinea pigs, and hamsters), rabbits, pigs, zebra fish, and non-human primates (NHPs; e.g., macaques and vervet monkeys) have been developed and are frequently used to investigate the multiple dynamics of host–microbiome interactions ( Gootenberg and Turnbaugh, 2011 ; Tlaskalova-Hogenova et al, 2014 ; Amato et al, 2015 ; National Academies of Sciences et al, 2018 ; Nagpal et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%